Reproduction of Local Strong Wind Area Induced in the Downstream of Small-Scale Terrain by Computational Fluid Dynamic (CFD) Approach. (4th December 2019) - Uchida, Takanori; Araki, Keiji
Abstract : In this research, the computational fluid dynamic (CFD) approach was applied for the solution of the problems of local strong wind areas in railway fields, and the mechanism of wind generation was discussed. The problem of local wind occurring on a railway line in winter was taken up in this research. A computational simulation for the prediction of wind conditions by large-eddy simulation (LES) was implemented, and it was clarified that local strong wind areas are mainly caused by separated flows originating from small-scale terrain positioned at its upstream (at approximately 180 m above sea level). Meanwhile, the effects of the size of the calculation area and spatial grid resolution on the result of calculation and the effect of atmospheric stability were also discussed. It was clarified that in order to simulate the air flow characteristic of the separated flow originating from the small-scale terrain (at an altitude of approximately 180 m) targeted in the present research, approximately 10 m of spatial resolution of computational cell in the horizontal direction is required. In addition, the effect of stable stratification on the flow was also examined. As a result, lee waves were excited at the downstream of the terrain over time in the case of stably stratified flow (Fr = 1.0). The reverse-flow region lying behind the terrain, which had been observed at a neutral time, was strongly inhibited. Consequently, a local strong wind area was generated at the downstream of the terrain, and a strong wind area passing through the observation mast was observed. By investigating the increasing rate of speed of the local strong wind area induced at the time of stable stratification, it was found that the wind was approximately 1.2 times stronger than what was generated at a neutral time.